Особливості функціонування конституційної скарги в Республіці Польща - Шевчук, І.; Shevchuk, I. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті досліджено особливості функціонування конституційної скарги в Республіці Польща. З’ясовано роль інституту конституційної скарги в системі конституційного судочинства. Визначено правовий механізм функціонування конституційної скарги в Республіці Польща. Проаналізовано перспективи впровадження інституту конституційної скарги в Україні з урахуванням польського досвіду. The article is devoted to the peculiarities of constitutional complaint functioning in the Republic of Poland. It was determined that the subjects of appeal to the Constitutional Tribunal with constitutional complaint are the individuals (citizens of the Republic of Poland, foreigners, stateless individuals) and entities (political parties, trade unions, businesses), but only in that area, in which they may be subject to constitutional rights and freedoms. It was determined that constitutional complaint is aimed to protect not all the rights, but only those defined by the Main Law. Constitutional complaint can be presented only after using all the legal means for protection of violated rights, in particular after providing to the applicant the verdict that came into force, the final decision or other final document. It was determined that the decision of Constitutional Tribunal of law or other normative act non-compliance according to the Constitution of the Republic of Poland causes the loss of its universal mandatory force. The person who filed a constitutional complaint, and other individuals affected by the act that was declared as unconstitutional may require the court or other authority to review the adopted decisions. It is indicated that the borrowing of Polish model of constitutional complaint by Ukraine does not require to radically change the existing system of constitutional justice in Ukraine, it also can help to avoid functions duplication of courts of general jurisdiction and the Constitutional Court of Ukraine.
Features of Constitutional Complaint Functioning in the Republic of Poland.
Keywords: конституційна скарга; модель конституційної скарги; Конституційний Трибунал; Конституція Республіки Польща; Конституційний Суд України; constitutional complaint; model of constitutional complaint; Constitutional Tribunal; Constitution of Republic of Poland; the Constitutional Court of Ukraine